Perkembangan Implementasi Logistik Halal Pada Perusahaan Kurir di Indonesia - agnes vicky; Feby Gusti Dendra; Milawati (Jurnal Industri dan Teknologi Samawa, 2025)
The concept of halal logistics is getting more attention, especially in the field of distribution and transportation, in line with the increasing demand for halal products in the global market. This study aims to determine the development of the implementation of halal logistics in courier companies in Indonesia using the method of review and literature study. Currently, there are technologies such as the Internet of Things (IoT) and blockchain to help in halal logistics tracking and traceability systems, which can open up opportunities for further innovation in the logistics sector. In Indonesia, there is only one courier company that already has halal certification. However, in its implementation, of course, there are still many problems and challenges faced. One of the biggest challenges is the lack of understanding of halal logistics concepts and standards among courier companies and industry players. Many courier companies do not fully understand halal requirements, both in terms of storage, transportation, and product handling. With a commitment to meeting halal standards and using the right technology, courier companies in Indonesia have a great opportunity to play a more strategic role in supporting halal supply chains domestically and around the world.